Tawhid in Arabic Persfective: Semantic Studies - Mardhatillah Syahril; Salamuddin Salamuddin (Universitas Muhammadiyah Enrekang, 2023)
This research was conducted to examine the meaning of the word Tawhid in the Arabic language perspective and understand in depth the nature of the word Tawhid in various semantic linguistic perspectives of the Arabic language. This research is a qualitative research with the method used, namely the descriptive method of analysis. The method is used in analyzing the word Tawhid in various perspectives, especially in the Arabic perspective. The meaning of Tawhid contained in several Arabic dictionaries is very varied. Researchers use semantic analysis derived from several dictionaries, sharaf books, and the perspectives of experts who can be analyzed that the word